The Effect of Drill Serve Forehand Training on Badminton Forehand Serve Accuracy Results - Motik, Dewi; Victorian, Ahmad Richard; Hartati, Hartati (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This research aims to determine the Forhand Drill Service Training Method on Badminton Forhand Service Accuracy Results in PB PUSRI Palembang Athletes. The type of research used is experimental and with a research design using one group pretest and post test design experiments. PB Pusri Palembang athlete research population. The sample in this study were PB PUSRI Palembang athletes, totaling 30 athletes. The instrument used is the forhand serve assessment test. The data analysis technique is processed using the T test. Based on the results of the T test, the count is > 22.284 with a t table of 2.045, with a confidence level of 0.95 or 95% (α=0.05). So there is a difference after doing it, the data for the two groups of forehand service pretest and forehand service posttest have significant differences regarding forehand service. This research concludes that there is an influence of the forehand serve drill on the results of badminton forehand serve accuracy in PB PUSRI Palembang athletes.